Measurement of self-esteem: comparison between the constructs of West and Islam - Ismail, Khaidzir; Anwar, Khairil; Hamsan, Hanina Halimatusaadiah (Center for Promoting Ideas, 2011)
The purpose of this paper is to discuss the results of a comparative study of constructs within the measurement of Western and Muslim construct. Rosenberg’s Self-Esteem Scale has been used to analyze the sources of western civilization, and this construct is one of the tools most widely used in the local psychological studies in Malaysia. The study involved a sample of 490 youths, aged between 15 and 21 years, from rehabilitation centers of Peninsular Malaysia. By using content analysis and statistical approach, the measurement tool of self-esteem was compared with that of Islamic psychosocial where the construct derived from is based on the Qur'an and Sunnah. Through this content analysis, we found that the items contained in self-esteem are closer to the concept of 'ujub (pride), which is contrary to Islamic principles. With the statistical approach, although not significant, the measurement of self-esteem might have showed the presence of the negative index (r = -0.052) when correlated with the measurement of Islam psychosocial. This indicates that higher Islam psychosocial has reduced the level of individual self-esteem. In terms of types and levels of misconduct, the higher levels of adolescent delinquency trends are found to indicate that the self-esteem is higher. Different from the psychosocial measurement tool of Islam, the higher level of misconduct is found to be a tendency toward the lower level of teenage psychosocial. The findings are expected to be a psychological study of the movement among Muslims Islam, which should use the approach of Islam.